Role of Metal Ions on Laser Interaction with a Conjugated Organic System - R. Amin, Ragab; S. Al-Naimi, Ibrahim; Z. Ismail, Lotfi (Asian Journal of Chemistry, 2010)
1,1 ,4,4-Buta-1 ,3-diene tetrasalicylocarbohydrazone H8BTSTCHand its metal complexes with Co(lI), Cu(II), Zn(II) and Pb(II) ionswere synthesized. The stoichiometry and structure of the ligand andits complexes were elucidated by elemental analysis as well as GC,IR and 1H-NMR spectroscopic techniques. Solution absorptionspectra, (in DMF), of the isolated compounds showed absorptionmanifold in the UV region with some tailing extending into thevisible. Laser excitation of these solutions at 410 nm resulted in alaser induced fluorescence, (LIF), arround 510 nm with the leadcomplex showing double the fluorescence intensity of both theligand and the Zn complex. The observed emissions from all thecompounds had similar features. In acidic buffer solutions, all isolatedcompounds showed enhanced emission intensities. Such enhancementmay be attributed to an increased coplanarity and theformation of molecular aggregates through H-bonding.